The phosphorylation of Pak1 by Erk1/2 to drive cell migration requires Arl4D acting as a scaffolding protein - Chang, Ting-Wei; Lin, Ming-Chieh; Yu, Chia-Jung; Lee, Fang-Jen S. (Journal of cell science, 2025)
Activation of extracellular signal-regulated kinases 1 and 2 (Erk1/2; also known as MAPK3 and MAPK1, respectively) at the plasma membrane usually leads to their translocation to various intracellular sites, where scaffolding proteins mediate substrate targeting. However, in platelet-derived growth factor (PDGF)-induced signaling, Erk1/2 phosphorylate Pak1 to drive cell migration while remaining at the plasma membrane, raising the question of whether scaffolding proteins are required. Similarly, the small GTPase Arf-like protein 4D (Arl4D) promotes cell migration by recruiting Pak1 to the plasma membrane and facilitating its phosphorylation, although the mechanism linking recruitment to phosphorylation remains unclear. To address these questions, we show that Arl4D functions as a scaffolding protein by recruiting Erk1/2 and Pak1 to the plasma membrane, assembling them into a functional complex. This complex allows Erk1/2 to phosphorylate Pak1, supporting the role of the latter in cell migration. Our findings identify Arl4D as a novel regulator of Erk1/2, reveal a conserved role of scaffolding proteins in Erk1/2 substrate targeting, and uncover an unrecognized interplay among Arl4D, Erk1/2 and Pak1. These insights provide a deeper understanding of the molecular coordination underlying Pak1-mediated cell migration and its regulation by Erk1/2 and Arl4D.